Evaluasi Sistem Informasi Rawat Inap dengan Metode Human Organization and Technology (HOT-FIT ) di Rumah Sakit Jember Klinik - Farah Dilla Wulandari; Ervina Rachmawati; Dony Setiawan Hendyca Putra; Mochammad Choirur Roziqin (Indonesian Journal Publisher, 2024)
Jember Klinik Hospital has been using SIMRS since 2012 to help the process of service to patients, but when implemented, there are still obstacles encountered, namely data derived from SIMRS (Hospital Management Information System) needs to be processed manually again, the monitor screen turns off, there is no educational SPO and socialization efforts have not reached an optimal level. The purpose of this study was to evaluate the Hospital Management Information System (SIMRS) of the inpatient unit using the Human Organization Technology (HOT-FIT) method and apply a cross-sectional research design and quantitative analysis at Jember Klinik Hospital. The sample size was 84 respondents utilizing a Lemeshow formula, the sampling method was by applying proportionate stratified random sampling. The results showed that there was a significant and strong relationship between information quality with system use and user satisfaction, a strong relationship between service quality and user satisfaction, a strong relationship between organizational structure and user satisfaction, a strong relationship between leadership support and system use.